Use of the Impella 2.5 left ventricular assist device in a patient with cardiogenic shock secondary to takotsubo cardiomyopathy. (7th May 2015) - Rashed, Ahmed; Won, Sekon; Saad, Marwan; Schreiber, Theodore
Abstract : We report a case of cardiogenic shock, believed to be secondary to stress-induced cardiomyopathy, managed by an Impella 2.5 assist device. Apical ballooning pattern was evident on left ventriculogram with no significant coronary artery disease on coronary angiography. Cardiogenic shock was initially managed medically with inotropes and vasopressors, but because the patient was clinically deteriorating, an Impella 2.5 left ventricular assist device was implanted. Remarkable recovery occurred within 48 h of implantation with significant increase in ejection fraction and only minimal residual apical hypokinesis observed on repeat ventriculogram.